Enhancing Patient Outcomes Through Team-Based Care: A Collaboration Between Physicians, Nurses, Pharmacists, Dentists, Laboratory, and Health Security Experts - Alhawsawi, Jehan Mosa Essa; Albariqi, Abdullah Mohamed Ahmed; Alshab, Duaa Ahmed; Ishgi, Ammar Ali; Asiri, Sharifah Ali; Albalawi, Atif Abdullah Aish; Albalawi, Musallam Suaykir M; Alenezi, Hanadi Ghadeer; Alruwaili, Mohammed Farhan Moail; Aldossari, Malak Fahad; et al. (Journal of Posthumanism, 2024)
Healthcare delivery increasingly relies on interdisciplinary collaboration to address complex and interrelated patient needs. While the benefits of integrating diverse professional roles are well documented, limited research has examined the impact of incorporating sleep disorder assessment and management into structured team-based care. Sleep disturbances—such as insomnia, obstructive sleep apnea, and circadian rhythm disorders—are prevalent among hospitalized patients and can significantly affect recovery, adherence, and overall well-being. This study investigates how interdisciplinary teams—including physicians, nurses, pharmacists, dentists, sleep medicine specialists, and health security experts—affect patient outcomes in healthcare institutions across Saudi Arabia. A mixed-methods approach was employed across tertiary hospitals and primary care centers, involving 150 patients and 50 healthcare professionals. Quantitative data were collected through patient records, satisfaction surveys, and validated sleep assessment tools, including the Pittsburgh Sleep Quality Index (PSQI) and Epworth Sleepiness Scale (ESS). Qualitative insights were gathered via interviews and focus groups. Statistical analysis used t-tests, chi-square tests, and regression modeling, while thematic analysis identified key enablers and barriers to integrated care delivery Patients receiving structured team-based care demonstrated significantly shorter hospital stays (mean = 4.3 days), lower 30-day readmission rates (8.0%), higher medication adherence (92.5%), and greater satisfaction scores (4.7/5) compared to those receiving traditional care (p < 0.05). They also showed better sleep quality, with lower PSQI scores and a higher proportion achieving good sleep status. Qualitative findings revealed that early identification and management of sleep disturbances—facilitated by interdisciplinary collaboration—were linked to improved rest, enhanced recovery, and greater patient confidence in care. Integrating sleep disorder assessment and management into structured, interdisciplinary healthcare teams enhances patient outcomes beyond traditional measures, contributing to faster recovery, higher satisfaction, and greater system efficiency. These findings support the adoption of care models that systematically address sleep health as a core component of patient-centered care.